2010
DOI: 10.1111/j.1365-2966.2010.17794.x
|View full text |Cite
|
Sign up to set email alerts
|

The SAGE-Spec Spitzer Legacy programme: the life-cycle of dust and gas in the Large Magellanic Cloud - Point source classification I

Abstract: We present the classification of 197 point sources observed with the Infrared Spectrograph in the SAGE-Spec Legacy programme on the Spitzer Space Telescope. We introduce a decisiontree method of object classification based on infrared spectral features, continuum and spectral energy distribution shape, bolometric luminosity, cluster membership and variability information, which is used to classify the SAGE-Spec sample of point sources. The decision tree has a broad application to mid-infrared spectroscopic sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 99 publications
(64 citation statements)
references
References 171 publications
(201 reference statements)
1
63
0
Order By: Relevance
“…Detailed spectroscopic analyses of the photospheres will allow testing of the chemical enrichment predictions of AGB theoretical models in full detail with a well constrained A90, page 26 of 45 sample of objects with known luminosities (and hence final and initial masses). Systematic IR spectroscopic surveys were defined before the construction of our catalogue, but the available Spitzer spectra (Kemper et al 2010;Woods et al 2011) form an ideal complement that is needed to fully characterise the post-AGB stars. -We have shown that light curves provide useful information on whether a post-AGB candidate is indeed a genuine post-AGB star.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed spectroscopic analyses of the photospheres will allow testing of the chemical enrichment predictions of AGB theoretical models in full detail with a well constrained A90, page 26 of 45 sample of objects with known luminosities (and hence final and initial masses). Systematic IR spectroscopic surveys were defined before the construction of our catalogue, but the available Spitzer spectra (Kemper et al 2010;Woods et al 2011) form an ideal complement that is needed to fully characterise the post-AGB stars. -We have shown that light curves provide useful information on whether a post-AGB candidate is indeed a genuine post-AGB star.…”
Section: Discussionmentioning
confidence: 99%
“…Their broad range of colours means that C-type stars in particular are likely to be seen on either side of this colour boundary and the cut at (J − K) 0 = 1.15 mag may well represent the red limit for the majority of the M-type population rather better than the blue limit for the C-type population (Kacharov et al 2012;Sibbons et al 2014). Although in rare cases very M-type stars with (J − K) colours much redder than this have been found (Woods et al 2011), such a colour cut is appropriate for an initial estimate of the global C/M ratio, as is the aim of this work. Spectroscopic data would be required in order to refine the classification of individual stars.…”
Section: Colour Selection 331 C-and M-type Agb Starsmentioning
confidence: 99%
“…These plots demonstrate that the GRAMS grid is able to reproduce the range of observed colors for carbon star candidates. We also include sources from the SAGE-Spec study that display molecular features and/or dust signatures typical of carbon stars (Kemper et al 2010;Woods et al 2011). Only the subset of SAGE-Spec sources that had a full 5−37 μm spectrum are shown here.…”
Section: Color-magnitude and Color-color Diagramsmentioning
confidence: 99%